PENGARUH KECERDASAN EMOSIONAL DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN CV. INDONESIA LIVE GARMENT KABUPATEN SRAGEN - Nurhanifah, Alvi; Aji, Ambyah Atas (Widya Dharma Journal of Business - WIJoB, 2022)
This study aimed to determine the significant effect of emotional intelligence and communication on employee performance CV. Indonesia Live Garment Districts Sragen both partialy and simultaneously. This research is quantitative research. Population in this study are all employess CV. Indonesia Live Garment Districts Sragen. The sampling technique that used is saturated sampling technique with 65 respondents. Primary data was obtained based on the results of the answer to the questionnaires distributed to the respondents. Analysis of the data in this study used multiple linear regression analysis, t-test, F-test and coefficient of determination (R2) using SPSS version 26. The results of the study indicate that partially emotional intelligence and communication variables have a significant effect on employee performance with the regression coefficient value on variables of emotional intelligence (0,255) and communication (0,602) and t-value of the emotional intelligence variable (2,324) and communication (5,411). Simultaneously the variables of emotional intelligence and communication affect employee performance with F-value (30,512).